2021
DOI: 10.3389/fvets.2021.759812
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Replication Inhibitory Effects of Tea Tree Oil on Vesicular Stomatitis Virus and Anti-inflammatory Activities in Vero Cells

Abstract: Viral disease management has been proven difficult, and there are no broadly licensed vaccines or therapeutics. Vesicular stomatitis virus (VSV) is an active pathogen of wild ungulates and livestock; its infection frequently caused irreversible vesicles on the tongue or other positions, leading to enormous economic loss. Tea tree oil (TTO) has been shown to be a popular remedy for many skin diseases owing to its antibacterial, antipruritic, and anti-inflammatory effects. However, the potential effect of TTO on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Many studies have found that TTO can inhibit LPS- [ 14 , 15 ], bacteria- [ 16 ], and Indiana vesiculovirus- [ 17 ] induced host cell inflammation. TTO has diverse components, which mainly include T-4-O, γ-terpinene, α-terpineol, and 1,8-cineole [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that TTO can inhibit LPS- [ 14 , 15 ], bacteria- [ 16 ], and Indiana vesiculovirus- [ 17 ] induced host cell inflammation. TTO has diverse components, which mainly include T-4-O, γ-terpinene, α-terpineol, and 1,8-cineole [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growth performance is an important indicator to assess animal growth and the efficacy of supplements in the poultry industry. Tea tree oil has been reported to have broad-spectrum antibacterial functions ( Carson et al, 2006 ) as well as antioxidant properties ( Souza et al, 2018 ), antitumor effects ( Clark et al, 2021 ), and anti-inflammation activity ( Shao et al, 2021 ). TTO is used extensively as a daily supplement for medical care and oral health in human medicine ( Lee et al, 2017 ; Salvatori et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shao et al showed that TTO has a blocking effect on vesicular stomatitis virus (VSV) replication at the gene and protein level. This offers potential for its use in the control of SARS-CoV-2 virus, and relevant experiments can be conducted to validate it [ 114 ]. Miyaoka et al have demonstrated that spraying on aerosols with acidic hypochlorite water (SAHW) can lower viral activity and hence prevent infections [ 115 ].…”
Section: Sampling Techniques and Devices Of Airborne Virusesmentioning
confidence: 99%